Abdominal cocoon with early postoperative small bowel obstruction: A case report and review of literature in China. Issue 25 (June 2018) - Xia, Jie; Xie, WeiJia; Chen, Li; Liu, Daren
Abstract: Rationale: Abdominal cocoon is a condition in which intestinal obstruction results from the encasement of part or whole of the small bowel by a thick fibrous membrane, giving the appearance of a cocoon. The preoperative diagnosis is difficult to be made and the treatment is still controversial. Patient concerns: Here we describe the case of a 62-year-old male presented with a 24-h history of continual colicky abdominal pain, which was accompanied with nausea and vomiting. Diagnosis: Accurate diagnosis of abdominal cocoon was made intraoperatively. Interventions: Membrane excision and adhesiolysis were performed and the patient experienced early postoperative small bowel obstruction. Nasointestinal obstruction tube was then installed and bowel function was gradually recovered by the 20th postoperative day. Outcomes: The patient recovered well and was discharged from the hospital on the 30th postoperative day Lessons: Abdominal cocoon can occur at any age. The possibility of abdominal cocoon should also be considered in infertile patients. Imaging studies may be helpful to make the correct diagnosis, and surgery should be performed for patients with recurrent acute or chronic intestinal obstruction.